Germinal Center B Cells Are Essential for Collagen‐Induced Arthritis. Issue 2 (22nd January 2018) - Dahdah, Albert; Habir, Katrin; Nandakumar, Kutty Selva; Saxena, Amit; Xu, Bingze; Holmdahl, Rikard; Malin, Stephen
Abstract : Objective: Rheumatoid arthritis (RA) is considered to be a prototypical autoimmune disorder. Several mechanisms have been proposed for the known pathologic function of B cells in RA, including antigen presentation, cytokine secretion, and humoral immunity. The aim of this study was to address the function of B lymphocytes in experimental arthritis. Methods: We mapped the adaptive immune response following collagen‐induced arthritis (CIA). We subsequently monitored these responses and disease outcomes in genetically modified mouse strains that lack mature B cell or germinal center (GC) functionality in a B cell–intrinsic manner. Results: Following primary immunization, the draining lymph nodes broadly reacted against type II collagen (CII) with the formation of GCs and T cell activation. Mice that lacked mature B cell function were fully protected against CIA and had a severely attenuated ability to mount isotype‐switched humoral immune responses against CII. Almost identical results were observed in mice that were selectively deficient in GC responses. Importantly, GC‐deficient mice were fully susceptible to collagen antibody–induced arthritis. Conclusion: We identified GC formation and anticollagen antibody production as the key pathogenic functions of B cells in CIA. The role of B cells in RA is likely to be more complex. However, targeting the GC reaction could allow for therapeutic interventions that are more refined than general B cell depletion.